Durability of per-oral endoscopic myotomy beyond 6 years - AbiMansour, Jad P.; Ichkhanian, Yervant; Minami, Hitomi; Familiari, Pietro; Landi, Rosario; Costamagna, Guido; Seewald, Stefan; Callahan, Zachary M.; Ujiki, Michael B.; Pioche, Mathieu; Ponchon, Thierry; Roman, Sabine; Cho, Joo Young; Yoo, In Kyung; Sippey, Megan; Marks, Jeffrey M.; Eleftheriadis, Nikolas; Khumbari, Vivek; Gutierrez, Olaya I. Brewer; Khashab, Mouen A. (Endoscopy International Open, 2021)
Background and study aims The aim of this study was to assess long-term clinical outcomes beyond 6 years in patients who underwent per-oral endoscopic myotomy (POEM) for the treatment of achalasia.Patients and methods Patients with achalasia who underwent POEM between 2010 and 2012 and had follow-up of at least 6 years were retrospectively identified at eight tertiary care centers. The primary outcome evaluated was clinical success defined by an Eckardt symptom score (ESS) ≤ 3 for the duration of the follow-up period. The clinical success cohort was compared to failure (ESS > 3 at any time during follow-up) in order to identify characteristics associated with symptom relapse. The incidence of patient-reported gastroesophageal reflux (GER) was also evaluated. Results Seventy-three patients with 6-year follow-up data were identified. Sustained clinical remission was noted in 89 % (65/73) at 6-years. Mean ESS decreased from 7.1 ± 2.3 pre-procedure to 1.1 ± 1.1 at 6 years (P < 0.001). Symptomatic reflux was reported by 27 of 72 patients (37.5 %). Type I achalasia (OR 10.8, P = 0.04) was found to be associated with clinical failure on logistic regression analysis. Conclusions In patients with achalasia, POEM provides high initial clinical success with excellent long-term outcomes. There are high rates of patient-reported gastroesophageal reflux post-procedure which persist at long-term follow-up.